PERMASALAHAN TERKAIT PENGGUNAAN OBAT (DRUG RELATED PROBLEM) PADA PASIEN LANSIA DI NEGARA-NEGARA BERKEMBANG - Islami, Afif (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The global geriatric population is rapidly increasing, particularly in developing countries, leading to higher burdens of chronic diseases and polypharmacy, which elevate drug-related problems (DRPs). This narrative review aims to comprehensively analyze DRPs among elderly patients in developing countries from 2015-2025, focusing on prevalence, risk factors, and interventions. Population comprised primary studies on geriatric patients (≥60 years) from Indonesia, India, Ethiopia, Vietnam, and Malaysia; purposive sample included 20 selected studies. Instruments involved systematic literature search protocols using keywords like "Drug Related Problems" and Boolean operators across PubMed, Scopus, Google Scholar, and ScienceDirect. Thematic content analysis classified DRPs per PCNE/APS-Doc categories, followed by narrative synthesis. Results revealed high DRP prevalence (41-82%), dominated by drug interactions, inappropriate dosing, and selection errors, driven by polypharmacy and multimorbidity. Clinical pharmacy interventions significantly reduced DRPs with 85-95% physician acceptance. In conclusion, multidisciplinary optimization and deprescribing enhance therapy safety and quality of life, warranting routine implementation in resource-limited settings.